HEXOKINASE1 signalling promotes shoot branching and interacts with cytokinin and strigolactone pathways. Issue 3 (2nd June 2021) - Barbier, Francois F.; Cao, Da; Fichtner, Franziska; Weiste, Christoph; Perez‐Garcia, Maria‐Dolores; Caradeuc, Mathieu; Le Gourrierec, José; Sakr, Soulaiman; Beveridge, Christine A.
Summary: Plant architecture is controlled by several endogenous signals including hormones and sugars. However, only little information is known about the nature and roles of the sugar signalling pathways in this process. Here we test whether the sugar signalling pathway mediated by HEXOKINASE1 (HXK1) is involved in the control of shoot branching. To test the involvement of HXK1 in shoot branching and in the hormonal network controlling this process, we modulated the HXK1 pathway using physiological and genetic approaches in rose, pea and arabidopsis. Mannose‐induced HXK signalling triggered bud outgrowth in rose and pea. In arabidopsis, both HXK1 deficiency and defoliation led to decreased shoot branching and conferred hypersensitivity to auxin. Complementation of the HXK1 knockout mutant gin2 with a catalytically inactive HXK1, restored shoot branching to the wild‐type level. HXK1‐deficient plants displayed decreased cytokinin levels and increased expression of MAX2, which is required for strigolactone signalling. The branching phenotype of HXK1‐deficient plants could be partly restored by cytokinin treatment and strigolactone deficiency could override the negative impact of HXK1 deficiency on shoot branching. Our observations demonstrate that HXK1 signalling contributes to the regulation of shoot branching and interacts with hormones to modulate plant architecture.